2015
DOI: 10.5219/524
|View full text |Cite
|
Sign up to set email alerts
|

Content of total polyphenols and antioxidant activity in selected varieties of onion (Allium cepa L.)

Abstract: Onion (Allium cepa L.) is one of the most important vegetable crops widely consumed in the world. The bulb onion is grown as fresh shoots and as bulbs for consuming uncooked, cooked, and pickled or production of seed and sets. They can be eaten raw, boiled, steamed and roasted. Onion has high nutritional value. Onions are a good source of vitamins, minerals and major component like polyphenols, flavonoids, fructooligosaccharides, thiosulfinates and other sulfur compounds. Polyphenols belong to significant anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
6
2
Order By: Relevance
“…Fratianni et al [2014] states for lentils variety San Gerardo 1098 µg g -1 , Colliano 1594 µg g -1 and for chickpea Sassano 147 µg g -1 , Castelcivita 183 µg g -1 . Our results are in contrary with experiments of Kavalcová et al [2014a], suggested that doses of the Se did not have significant effect on the content of polyphenols. In the trial with onion they applied Se in the form of sodium selenate in different form, there was applicated into soil.…”
Section: Total Polyphenol Content (Tpc)contrasting
confidence: 57%
“…Fratianni et al [2014] states for lentils variety San Gerardo 1098 µg g -1 , Colliano 1594 µg g -1 and for chickpea Sassano 147 µg g -1 , Castelcivita 183 µg g -1 . Our results are in contrary with experiments of Kavalcová et al [2014a], suggested that doses of the Se did not have significant effect on the content of polyphenols. In the trial with onion they applied Se in the form of sodium selenate in different form, there was applicated into soil.…”
Section: Total Polyphenol Content (Tpc)contrasting
confidence: 57%
“…Our results are in contrary with experiments of Kavalcová et al [2014a], suggested that doses of the Se did not have significant effect on the content of polyphenols. In the trial with onion they applied Se in the form of sodium selenate in different form, there .…”
Section: Total Polyphenol Content (Tpc)contrasting
confidence: 99%
“…10 Polyphenols are a large group of chemical compounds with subgroups including flavonoids and anthocyanins. [11][12][13] Phenolic compounds may inhibit lipid oxidation as free radical scavengers and metal ion chelators. 14 Onions are well known as a rich source of polyphenols including flavonoids that increases the antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%
“…15 The high contents of onion flavonoids consist of quercetin aglycone and its glycosides. 12,15,16 Flavonoids tend to accumulate in outer peel (bulb skin) of onions.…”
Section: Introductionmentioning
confidence: 99%